Impact of crossflow microfiltration on aroma and sensory profiles of a potential functional citrus‐based food. (25th April 2022) - Hammad, Imane; Dornier, Manuel; Lebrun, Marc; Maraval, Isabelle; Poucheret, Patrick; Dhuique‐Mayer, Claudie
Abstract: BACKGROUND: Citrus juices can be cold‐concentrated by crossflow microfiltration (CMF) in order to obtain functional foods enriched in carotenoids, flavonoids and pectins. The work aimed to characterize the organoleptic quality of this type of micronutrient‐dense foods through their aroma profile and sensory analysis. Two citrus concentrates with and without a diafiltration step were compared. RESULTS: Both citrus products were very different, linked to aroma compound, sugar and organic acid contents. Due to its sugar/acidity balance and its better aromatic profile responsible for the citrus–floral flavour, the concentrate without diafiltration was preferred by the sensory panel. Thanks to a simple transfer model, we showed that retention of volatiles clearly varied from one aroma compound to another. The terpene hydrocarbons were the most retained by the membrane during CMF, probably because they were strongly associated with insoluble solids by adsorption. CONCLUSION: Even though the process modified their organoleptic profiles, both citrus‐based products were well rated and can be consumed directly as pleasant functional drinks. © 2022 Society of Chemical Industry.